A Integration of Next-Generation Sequencing in Health Biotechnology: A Systematic Synthesis and Meta-Analysis of Diagnostic, Clinical, and Economic Impacts. - Adabi Darban; Akram caesar Maulana; Rachmawati Rachmawati (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Technological development Next-Generation Sequencing(NGS) has revolutionized the fields of molecular diagnostics and healthcare biotechnology through comprehensive, high-throughput, and precision genomic approaches. This study aims to systematically synthesize scientific evidence on the diagnostic, clinical, and economic impact of NGS implementation in modern healthcare. The methods used areSystematic Literature Review(SLR) with reference to the PRISMA guidelines, using the Scopus database for the 2020–2026 publication period. Of the 3,491 identified articles, 20 met the inclusion criteria and were analyzed qualitatively. The synthesis results showed that NGS significantly improves diagnostic sensitivity and accuracy, accelerates diagnosis, and supports the application of precision medicine, particularly in genetic diseases, cancer, and infections. Furthermore, the implementation of NGS has been shown to provide clinical benefits in the form of improved patient outcomes and therapy efficiency, and demonstrates potentialcost-effectivenesslong-term. However, challenges related to regulation, ethics, genomic data privacy, and access disparities remain major concerns. Overall, NGS is a crucial pillar in the sustainable transformation of genomics-based health systems.